TEACHERS’ TALK IN TEACHING ENGLISH: ROLES AND CHALLENGES - Ningsih, Fitri Randia; Daulay, Sholihatul Hamidah (TELL - US JOURNAL, 2023)
This study aimed to identify the most common teachers' talk in EFL classrooms as well as the reasons that influenced their selection. This research focused on the teacher's perception of how the teacher talks with students in class and some of the challenges that teachers might face while interacting with students to encourage students in the learning process to take place. The participants of this research were 2 English teachers who received professional training in English teaching as part of the undergraduate program. They were English teachers at an integrated Islamic school in Medan. The observations were made to describe the teacher interview process data and also the learning carried out by the teacher to find insights about how the teacher talks and what challenges the teacher faced when interacting with students in class. This study used a qualitative descriptive method. The findings in this study were that the teacher applied more dominant English communication as input. Teachers felt that increasing the use of the target language will be more challenging because it is influenced by several aspects, such as the motivation, attitude, and skills of the teacher and students. In addition, when the teacher spoke it varies greatly on several levels based on the factors that influence the teacher and student. The results of this study also showed that most teacher conversations are used in the form of questions, then explaining the lesson, giving directions to students, and praising or encouraging students. Apart from that, because students are considered as learners or beginners, class interaction must be adjusted to the right and appropriate choice of language so that communication becomes easier and more effective. In addition, the analysis of teachers’ talk in the classroom would be beneficial for teachers to plan and conduct enhanced learning situations.